A qualitative study of primary care physicians’ perceptions and experiences on iron-folic acid consumption - Joshi, Ankur; Bali, Surya; Kale, Saket; Tiwari, Sharad; Arutagi, Viswanath (International Journal Of Community Medicine And Public Health, 2017)
Background: A primary health centre (PHC) physician, because of his physician-provider interaction at community level and legitimate capacity to deliver and monitor health services, serves as an ideal candidate to understand the specific health/ health program related issues. Methods: This community based qualitative study was conducted in selected clusters of state of Madhya Pradesh (central India) identified through multileveled stratification. The physicians serving in primary health centres from the selected clusters were in depth interviewed through topic guides based upon conceptual construct. The data obtained through in-depth interviews was utilized for thematic framework and linkage association. Results: Two major interrelated themes emerged from the convergence of the user related and system related subthemes. The first major theme is “distorted perceptions reinforced by unpleasant encounters” which is constructed from the convergence of user concerns. The theme “system resistance and resource constraints” is assembled from convergence of system issues. Conclusions: On a policy perspective, all the attempts should be made to break the misconception around IFA supplementation and to augment the feeling of ownership in the community.